Preoperative circulating tumor cells level is associated with lymph node metastasis in patients with unifocal papillary thyroid carcinoma - Yihua Gu; Ming Yu; Jiaqin Deng; Yeqian Lai (World Journal of Surgical Oncology)
Abstract Objective Unifocal papillary thyroid carcinoma (PTC) refers to thyroid cancer that has only one isolated lesion, it has also the possibility of lymph node metastasis (LNM). Circulating tumor cell (CTC) has been used to assist in the assessment of tumor progression, but the relationship between CTCs levels and LNM in unifocal PTC patients is unclear. Methods The clinical records (age, gender, Hashimoto’s thyroiditis, thyroid function, tumor size, invaded capsule (thyroid cancer penetrating the capsule), clinical stage, and LNM) of unifocal PTC patients in Meizhou People’s Hospital were analyzed retrospectively. Receiver operating characteristic (ROC) curve analysis was used to determine the cutoff value of CTCs levels to distinguish LNM. The relationship between CTCs level and clinical features was analyzed. Logistic regression analysis was used to evaluate the relationship between CTCs and LNM. Results A total of 507 unifocal PTC patients were included, and 198(39.1%) patients with LNM. The critical value of CTCs was 9.25 FU/3mL by ROC analysis, and 288(56.8%) unifocal PTC patients with preoperative CTC-positive(≥ 9.25 FU/3mL). The patients with positive CTCs had higher proportions of normal thyroid function (91.3% vs. 84.5%, p = 0.018), and LNM (44.1% vs. 32.4%, p = 0.008) than patients with negative. High preoperative CTCs level (≥ 9.25/<9.25 FU/3mL, odds ratio(OR): 1.653, 95% confidence interval(CI): 1.115–2.451, p = 0.012), tumor size > 1 cm (OR: 3.189, 95% CI: 2.069–4.913, p < 0.001), and invaded capsule (OR: 1.521, 95% CI: 1.005–2.302, p = 0.047) were associated with LNM among unifocal PTC in multivariate logistic regression analysis. Conclusions High preoperative CTCs level (≥ 9.25 FU/3mL), tumor size > 1 cm, and invaded capsule were associated with LNM among unifocal PTC.